EFFECT OF PRANAYAMA ON PULMONARY FUNCTION TESTS AND BREATH HOLDING TIME IN MALE MEDICAL STUDENTS - Rastogi, Dolly; Saxena, Jalaj; Bhagat, Anumeha; Bhushan Mishra, Shashi; Rastogi, Munish; Saxena, Sonali (Indian Journal of Community Health, 2007)
.